2013
DOI: 10.1111/exd.12067
|View full text |Cite
|
Sign up to set email alerts
|

Galanin is a modulator of eccrine sweat gland secretion

Abstract: The neuropeptide galanin has been ascribed different roles in modulating physiological functions in the skin. The present study examined the function of galanin in eccrine sweat gland physiology. We demonstrated secretion of galanin by sweat glands in vivo by radioimmunoassay of human sweat (20-192 fmol galanin/ml). Furthermore, human sweat glands expressed galanin receptors GalR2 and GalR3. Using chamber short-circuit current (Isc) measurements showed that application of galanin to human NCL-SG3 cells led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 15 publications
(18 reference statements)
1
26
0
1
Order By: Relevance
“…Furthermore, GAL has functions in eccrine sweat gland physiology, because application of GAL to NCL-SG3 cells increased short-circuit (Isc) currents. Application of SNAP 37889 inhibited the effect of GAL on Isc currents, indicating that the observed GAL effects are mediated via GAL 3 receptors (24). Based on these results, we hypothesized that sudomotor function differs between GAL 3 -KO and WT mice.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, GAL has functions in eccrine sweat gland physiology, because application of GAL to NCL-SG3 cells increased short-circuit (Isc) currents. Application of SNAP 37889 inhibited the effect of GAL on Isc currents, indicating that the observed GAL effects are mediated via GAL 3 receptors (24). Based on these results, we hypothesized that sudomotor function differs between GAL 3 -KO and WT mice.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, it was reported that GAL and GAL 3 receptor are involved in eccrine sweat gland secretion (24,25). Because we found GAL 3 receptor to be involved in anxietyrelated behavior, and because sweating is influenced by anxiety, we investigated the role of GAL 3 receptor in sudomotor function.…”
Section: Analyses Of Molecular and Compensatory Mechanisms Of Behavioralmentioning
confidence: 96%
“…Recently, it was shown that the NCL-SG3 cell line derived from human eccrine sweat gland secretory epithelia expresses GAL mRNA (Bovell et al, 2013). Because this cell line produces galanin peptide immunoreactivity (B.…”
Section: B Skinmentioning
confidence: 99%
“…Because this cell line produces galanin peptide immunoreactivity (B. Holub and R. Lang, unpublished data) and galanin is present in human sweat at concentrations up to 10-fold higher than in serum (Bovell et al, 2013), it is likely that members of the galanin peptide family are secreted by eccrine sweat glands and transported to the skin surface to exert their antimicrobial activity, similar to other cutaneous antimicrobial peptides (Schittek et al, 2001;Murakami et al, 2002).…”
Section: B Skinmentioning
confidence: 99%
See 1 more Smart Citation